Role of Community Nursing Using an Aggregate Approach in School Health: A Literatur Review - M Bachtiar Safrudin; Risnawati Sari; Marlina Damayanti; Amanda Putri; Husnul Khotimah Mei Syahadati Saragih; Fadhila Zarifa Az-Zahra (CV. CENDIKIA JENIUS INDONESIA, 2025)
School-age children are a vulnerable group to various health problems that may affect learning processes and growth development. Schools, as part of the community, play an important role in promotive and preventive health efforts through an aggregate-based community nursing approach. This study aimed to analyze the role of community nursing using an aggregate approach in supporting school health. A literature review method was applied by reviewing scientific articles published between 2021 and 2025 through Google Scholar and PubMed, with five relevant articles selected for analysis. The findings indicate that community nursing interventions in schools, including health education, promotion of clean and healthy living behaviors, physical activity, and school-based health services, contribute positively to improving students, health knowledge, attitudes, and behaviors. The aggregate approach is considered effective in supporting school health and should be continuously developed through collaboration among nurses, schools, and the community.